The factor that influences consumer on patronization of Islamic Bank / Norsakinah Abdul Nasir - Abdul Nasir, Norsakinah (Faculty of Business Management, 2015)
THE FACTOR THAR INFLUENCES CONSUMER ON PATRONIZATION OF ISLAMIC BANK Malaysia had been practicing Islamic banking in 1983 due to establishment of Bank Islam Malaysia Berhad and Islamic Banking Act. Nowadays, Malaysia become a leader and role model to others countries that also that had implementing Islamic banking for a long time before Malaysia. Islamic banking Industry in Malaysia is slowly growing gradually but it management and operation is systematic and efficiently than other country nevertheless, Malaysia is become the first country that issue the first Sukuk in the world. Islamic banking in Malaysia is surviving its existence by competing with its counterpart of the conventional banking system. This is because, conventional banking has been deeply rooted in the world and Malaysia itself. The main objective of this research is to study the factor that influences consumer on patronization of Islamic bank. 115 questionnaires will be distributed to anyone that patronage Islamic bank. Considering this objective, there is independent variables in the theoretical framework to explain the decision of patronization of Islamic bank. The expected finding of this study will indicate the variable is significant with dependent variable. The data will be analyse by SPSS system.